Somatic embryogenesis from scutellar embryo of oryza sativa L. var. MR219 - Panjaitan, Syaiful Bahri; Abdullah, Siti Nor Akmar; Abdul Aziz, Maheran; Meon, Sariah; Omar, Othman (Universiti Putra Malaysia Press, 2009)
Somatic embryogenesis is an efficient plant regeneration system and it is a potentially useful tool for genetic transformation. An experiment was carried out on somatic embryogenesis from scutellar embryo of rice var. MR219. High intensity of callus formation (100%) was initiated through culturing the scutellar embryo on modified MS medium, with the macro nutrients reduced to half-strength and supplemented with different 2,4-D concentrations (1,2,4 and 6 mgL-1). Meanwhile, the highest percentage of embryogénie callus formation (80%) was obtained on the modified MS medium containing 4 mgL-12, 4-D. The calli produced were yellowish and friable with nodular structures on the surface. Rounded cells with highly dense cytoplasm were also observed under an inverted microscope and their viability was confirmed based on the apple green fluorescence staining in the fluorescein diacetate (FDA) solution. High mean number of somatic embryos was also produced in this treatment, at 85 somatic embryos per expiant. Upon transferring the somatic embryos onto the modified MS medium with 2 mgL-1 BAP and 0.05 mgL-1 NAA for germination, 82.5% of the somatic embryos were germinated into the seedlings.